mTORC1 activates SREBP-2 by suppressing cholesterol trafficking to lysosomes in mammalian cells - Eid, Walaa (Proc Natl Acad Sci U S A, 2017)
mTORC1 is known to activate sterol regulatory element-binding proteins (SREBPs) including SREBP-2, a master regulator of cholesterol synthesis. Through incompletely understood mechanisms, activated mTORC1 triggers translocation of SREBP-2, an endoplasmic reticulum (ER) resident protein, to the Golgi where SREBP-2 is cleaved to translocate to the nucleus and activate gene expression for cholesterol synthesis. Low ER cholesterol is a well-established trigger for SREBP-2 activation. We thus investigated whether mTORC1 activates SREBP-2 by reducing cholesterol delivery to the ER. We report here that mTORC1 activation is accompanied by low ER cholesterol and an increase of SREBP-2 activation. Conversely, a decrease in mTORC1 activity coincides with a rise in ER cholesterol and a decrease in SERBP-2 activity. This rise in ER cholesterol is of lysosomal origin: blocking the exit of cholesterol from lysosomes by U18666A or NPC1 siRNA prevents ER cholesterol from increasing and, consequently, SREBP-2 is activated without mTORC1 activation. Furthermore, when mTORC1 activity is low, cholesterol is delivered to lysosomes through two membrane trafficking pathways: autophagy and rerouting of endosomes to lysosomes. Indeed, with dual blockade of both pathways by Atg5(−/−) and dominant-negative rab5, ER cholesterol fails to increase when mTORC1 activity is low, and SREBP-2 is activated. Conversely, overexpressing constitutively active Atg7, which forces autophagy and raises ER cholesterol even when mTORC1 activity is high, suppresses SREBP-2 activation. We conclude that mTORC1 actively suppresses autophagy and maintains endosomal recycling, thereby preventing endosomes and autophagosomes from reaching lysosomes. This results in a reduction of cholesterol in the ER and activation of SREBP-2.